Human Immunodefiency Virus Infection in Tuberculosis Patients at Kotaraja Health Center of Papua - Herlando Sinaga; Ester Rampa; Anni Erna Woriori (Poltekkes Kemenkes Mataram, 2022)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells and causes the human immune system to decrease. Tuberculosis in HIV patients is an opportunistic infection that will aggravate the disease infection in patients. Examination of HIV (Human Immunodeficiency Virus) in Tuberculosis Patients was carried out at the Kotaraja Health Center. This study was conducted for 1 month starting from May 17, 2019, to June 07, 2019. The purpose of this study was to determine HIV in tuberculosis patients at the Kotaraja Health Center. This type of research is descriptive with a laboratory test approach. The sample used is a serum sample with a diagnosis of HIV. The method used in this examination is the Rapid Test method. The results of HIV testing on tuberculosis patients, sample data obtained from HIV tuberculosis co-infected respondents amounted to 30 HIV respondents who took tuberculosis treatment >6-9 months, negative 6 patients (20%).